2015
DOI: 10.1051/0004-6361/201526031
|View full text |Cite
|
Sign up to set email alerts
|

No variations in transit times for Qatar-1 b

Abstract: Aims. The transiting hot-Jupiter planet Qatar-1 b exhibits variations in transit times that could be perturbative. A hot Jupiter with a planetary companion on a nearby orbit would constitute an unprecedented planetary configuration, which is important for theories of the formation and evolution of planetary systems. We performed a photometric follow-up campaign to confirm or refute transit timing variations. Methods. We extend the baseline of transit observations by acquiring 18 new transit light curves acquir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…Binning was done to 70 points for each transit curve. Transit geometries are also plotted with the corresponding curves (see upper parts of the References Alsubai et al (2011) 0.1633 ± 0.0053 0.1454 ± 0.0015 83.47 ± 0.40 96.71 ± 1.11 von Essen et al (2013) 0.1558 ± 0.0024 0.1435 ± 0.0008 84.52 ± 0.24 - Covino et al (2013) 0.1601 ± 0.0025 0.1513 ± 0.0008 83.82 ± 0.25 97.63 ± 1.44 Mislis et al (2015) 0.1640 ± 0.0030 0.1475 ± 0.0009 84.03 ± 0.16 - Maciejewski et al (2015) 0.1582 ± 0.0017 0.1459 ± 0.0008 84.26 ± 0.17 98.50 ± 1.70 Collins et al (2015) 0.1600 ± 0.0018 0.1463 ± 0.0006 84.08 ± 0. As a measure of gravitational focusing, the Safronov number (Θ) given by Hansen and Barman (2007)…”
Section: Physical Propertiesmentioning
confidence: 97%
See 2 more Smart Citations
“…Binning was done to 70 points for each transit curve. Transit geometries are also plotted with the corresponding curves (see upper parts of the References Alsubai et al (2011) 0.1633 ± 0.0053 0.1454 ± 0.0015 83.47 ± 0.40 96.71 ± 1.11 von Essen et al (2013) 0.1558 ± 0.0024 0.1435 ± 0.0008 84.52 ± 0.24 - Covino et al (2013) 0.1601 ± 0.0025 0.1513 ± 0.0008 83.82 ± 0.25 97.63 ± 1.44 Mislis et al (2015) 0.1640 ± 0.0030 0.1475 ± 0.0009 84.03 ± 0.16 - Maciejewski et al (2015) 0.1582 ± 0.0017 0.1459 ± 0.0008 84.26 ± 0.17 98.50 ± 1.70 Collins et al (2015) 0.1600 ± 0.0018 0.1463 ± 0.0006 84.08 ± 0. As a measure of gravitational focusing, the Safronov number (Θ) given by Hansen and Barman (2007)…”
Section: Physical Propertiesmentioning
confidence: 97%
“…First TTV analysis presented by von Essen et al (2013) and they indicated a significant signal with a period of ∼ 190 days. However more recently, Maciejewski et al (2015) and Collins et al (2015) could not find evidence of an additional planet in the Qatar-1b system based on TTV analysis.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Mislis et al (2015) needed more precise data to detect the long-term TTVs found in von Es-sen et al (2013). Maciejewski et al (2015) concluded that the Qatar-1 system lacks any tertiary body able to produce periodic transit variations greater than 1 minute. Their analysis of the Qatar-1b orbital and planetary parameters do agree, however, with those of Covino et al (2013) and von Essen et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…So far, already more than 2653 extra-solar planetary systems have been found to transit their parent stars. In order to study the perturbation from small unknown planets and to constrain the overall orbital configuration in planetary systems, TTVs have been seriously investigated in recent years (Agol et al 2005;Holman et al 2005Holman et al , 2010Maciejewski et al 2015). Among the detected planetary systems, Qatar-1 attracts a lot of attention due to its strong transit signal and short orbital period.…”
Section: Introductionmentioning
confidence: 99%